2018
DOI: 10.15570/actaapa.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Cupping in dermatology: a critical review and update

Abstract: Cupping is an ancient procedure that has been practiced for thousands of years. It has been used to treat a variety of medical conditions, including dermatological ones. Cupping has been described in the literature for the treatment of conditions such as acne and eczema. The procedure is fundamentally divided into dry cupping and wet cupping; however, there have been many modern adaptations. Adverse events related to the procedure have been reported in the literature and should be considered by patients. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(36 reference statements)
0
14
0
2
Order By: Relevance
“… [15] CT includes several forms such as dry cupping, wet cupping, and others. [16] What's more, CT relieved the symptoms, and relapse of neurodermatitis has been reported for a long time. [ 17 18 ] Not only that, but CT also obtained satisfactory results involving fibromyalgia syndrome, [19] migraine headache, [20] psoriasis Vulgaris, [21] chronic urticaria, [22] and others.…”
Section: Introductionmentioning
confidence: 99%
“… [15] CT includes several forms such as dry cupping, wet cupping, and others. [16] What's more, CT relieved the symptoms, and relapse of neurodermatitis has been reported for a long time. [ 17 18 ] Not only that, but CT also obtained satisfactory results involving fibromyalgia syndrome, [19] migraine headache, [20] psoriasis Vulgaris, [21] chronic urticaria, [22] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Although both dry and wet cupping are widely used as alternative medicine methods, there is a paucity of reports on its efficacy and safety in the treatment of psoriasis. 2 To the best of our knowledge, 21 cases addressing the relationship between CT and Koebnerization have been reported to date (Table 1). [4][5][6][7] CT-triggered other dermatoses such as lichen planus, dermatitis herpetiformis, and seborrheic dermatitis have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In 16 RCS studies on neurodermatitis, herpes simplex, chronic urticaria, acne vulgaris, and acute eczema, results were obtained regarding the effectiveness of wet cupping therapy. In a review on skin diseases, it was concluded that "Although there is not enough study, cupping therapy is promising in skin diseases" [15,16]. When we look at the effectiveness of cupping therapy in nervous system diseases; there are results showing that it is effective in 15 RCSs performed in diseases such as facial paralysis, peroneal nerve palsy, cerebral palsy, brachial paresthesia, postherpetic neuralgia, migraine and trigeminal neuralgia [8,[17][18][19][20].…”
Section: ⅲ Findingsmentioning
confidence: 99%
“…In 16 RCS studies on skin diseases such as neurodermatitis, herpes simplex, chronic urticaria, acne vulgaris, and acute eczema, results were obtained regarding that cupping therapy was effective (Table 1) [15]. Cupping therapies were applied on and around the skin lesion in these studies.…”
Section: Survey Sajid Mi/ 2016 Englandmentioning
confidence: 99%